The Business Ethics of Kotagede’s Silver Entrepreneurs from the Kingdom to the Modern Era (History Department, Semarang State University and Historian Society of Indonesia, 2020)
The silver business since the reign of Sri Sultan HB VIII has gained its position in driving the economic progress of Kotagede’s people. The silver industry, besides its economic values, is also a cultural asset of the people of Yogyakarta. From 1935-1938, there were more than 78 silver entrepreneurs with a total annual production of 25 tons of silver. This study aims to determine and to analyze the history of the silver business in Kotagede and the values inherited from the kingdom period to the modern era. This research used the historical method by describing data on the development of silver business in Kotagede in a descriptive, chronological manner combined with a phenomenological approach. This research shows the success of the silver industry in Kotagede from the kingdom to the colonial era. It is supported by the collective power of the craftsmen community and silver entrepreneurs. It was also encouraged by the local government which helped to open the silver market network both at national and international levels. During the old order until the new order, the role of business actors in each founder of the silver business in building marketing networks both nationally and internationally became one of the main factors in running the silver industry in Kotagede. Third, the ethics inherited include honest, patient, simple, clean, neat, conscientious, healthy intentions, innovative, hard work. Bisnis perak sejak era pemerintahan Sri Sultan HB VIII telah mendapatkan posisi tersendiri dalam mendorong kemajuan ekonomi masyarakat Kotagede. Industri perak selain bernilai ekonomis tinggi dan potensial di pasar domestik maupun mancanegara juga menjadi aset budaya masyarakat Yogyakarta. Sejak 1935- 1938 terdapat lebih dari 78 pengusaha perak dengan total produksi tiap tahun 25 ton perak. Penelitian ini bertujuan mengetahui dan menganalisis sejarah perkembangan bisnis perak di Kotagede beserta nilai-nilai yang di wariskan dari era kerajaan sampai era modern. Penelitian ini menggunakan metode sejarah dengan memaparkan data-data perkembangan bisnis perak di Kotagede secara deskriptif, kronologis yang digabungkan dengan pendekatan fenomenologis. Penelitian ini menghasilkan beberapa temuan sebagai berikut. Pertama, kesuksesan perkembangan perak di Kotagede pada era kerajaan sampai kolonial selain ditopang oleh kekuatan kolektivitas komunitas pengrajin dan pengusaha perak juga didorong oleh pemerintah lokal yang membantu membuka jejaring pasar perak baik level nasional maupun internasional. Kedua, pada masa orde lama sampai orde baru peranan aktor-aktor bisnis pada masing-masing pendiri usaha perak dalam membangun jaringan pemasaran baik tingkat nasional maupun internasional menjadi salah satu faktor utama dalam menjalankan roda bisnis perak di Kotagede. Ketiga, etika yang diwariskan dalam bisnis perak diantaranya adalah: jujur, sabar, sederhana, bersih, rapi, teliti, niat kuat, inovatif, kerja keras.